Acinetobacter baumannii Catabolizes Ethanolamine in the Absence of a Metabolosome and Converts Cobinamide into Adenosylated Cobamides - Elizabeth A. Villa; Jorge C. Escalante-Semerena (mBio, 2022)
ABSTRACT Acinetobacter baumannii is an opportunistic pathogen typically associated with hospital-acquired infections. Our understanding of the metabolism and physiology of A. baumannii is limited. Here, we report that A. baumannii uses ethanolamine (EA) as the sole source of nitrogen and can use this aminoalcohol as a source of carbon and energy if the expression of the eutBC genes encoding ethanolamine ammonia-lyase (EAL) is increased. A strain with an ISAba1 element upstream of the eutBC genes efficiently used EA as a carbon and energy source. The A. baumannii EAL (AbEAL) enzyme supported the growth of a strain of Salmonella lacking the entire eut operon. Remarkably, the growth of the above-mentioned Salmonella strain did not require the metabolosome, the reactivase EutA enzyme, the EutE acetaldehyde dehydrogenase, or the addition of glutathione to the medium. Transmission electron micrographs showed that when Acinetobacter baumannii or Salmonella enterica subsp. enterica serovar Typhimurium strain LT2 synthesized AbEAL, the protein localized to the cell membrane. We also report that the A. baumannii genome encodes all of the enzymes needed for the assembly of the nucleotide loop of cobamides and that it uses these enzymes to synthesize different cobamides from the precursor cobinamide and several nucleobases. In the absence of exogenous nucleobases, the most abundant cobamide produced by A. baumannii was cobalamin. IMPORTANCE Acinetobacter baumannii is a Gram-negative bacterium commonly found in soil and water. A. baumannii is an opportunistic human pathogen, considered by the CDC to be a serious threat to human health due to the multidrug resistance commonly associated with this bacterium. Knowledge of the metabolic capabilities of A. baumannii is limited. The importance of the work reported here lies in the identification of ethanolamine catabolism occurring in the absence of a metabolosome structure. In other bacteria, this structure protects the cell against damage by acetaldehyde generated by the deamination of ethanolamine. In addition, the ethanolamine ammonia-lyase (EAL) enzyme of this bacterium is unique in that it does not require a reactivase enzyme to remain active. Importantly, we also demonstrate that the A. baumannii genome encodes the functions needed to assemble adenosylcobamide, the coenzyme of EAL, from the precursor cobinamide.